Buried treasures and ancient forges: a historical analysis of mines and ironworks in the Stilaro Valley - Fiorenza, Elia (European Scientific Journal (Kocani), 2024)
This study aims to delve into the mines and ironworks of the Stilaro Valley and the ancient ironworking processes that occurred there. Up until the late 19th century, the area encompassing the municipalities of Bivongi, Pazzano, Stilo, Fabrizia, Mongiana, and Guardavalle stood as one of southern Italy's foremost centers for iron production and mining. Drawing upon archaeological, historical, and archival sources, this research seeks to enrich our comprehension of the economic and industrial activities that define this region. Utilizing techniques such as direct source study and cross-referencing with literature on the subject, this investigation has consulted archival documents stored in the State Archives of Naples and the State Archives of Catanzaro. The historical and geological backdrop of the Stilaro Valley furnishes an insight into its mineral wealth and the intricate mining and ironworking undertakings spanning centuries. Historical evidence, bolstered by significant discoveries, suggests an ancient tradition of metalworking in the area, with its influence extending into Magna Graecia. The scrutiny of mines and ironworks unveils a nuanced dynamic of adaptation and interaction among ancient communities, whose migrations and settlements were shaped by the natural resources and economic prospects offered by the region. The significance of mines and ironworks transcends mere economic and industrial development; they also profoundly influenced the cultural and social fabric of ancient and medieval Calabria. Initiatives like the Ecomuseum of the Ironworks and Foundries of Calabria underscore the imperative of conserving and promoting this historical and industrial legacy for generations to come.